Exotic magnetic and electronic properties of layered CrI3 single crystals under high pressure - Ghosh, Anirudha; Singh, D.; Aramaki, T.; Mu, Qingge; Borisov, V.; Kvashnin, Y.; Haider, G.; Jonák, Martin; Chareev, D.; Medvedev, S. A.; Klingeler, Rüdiger; Mito, M.; et al. (Physical review, 2022)
Through advanced experimental techniques on CrI3 single crystals, we derive a pressure-temperature phase diagram. We find that Tc increases to ∼66 K with pressure up to ∼3 GPa followed by a decrease to ∼10 K at 21.2 GPa. The experimental results are reproduced by theoretical calculations based on density functional theory where electron-electron interactions are treated by a static on-site Hubbard U on Cr 3d orbitals. The origin of the pressure-induced reduction of the ordering temperature is associated with a decrease in the calculated bond angle, from 95∘ at ambient pressure to ∼85∘ at 25 GPa. Above 22 GPa, experiment and theory jointly point to the idea that the ferromagnetically ordered state is destroyed, giving rise first to a complex, unknown magnetic configuration, and at sufficiently high pressures a pure antiferromagnetic configuration. This sequence of transitions in the magnetism is accompanied by a well-detected pressure-induced semiconductor-to-metal phase transition that is revealed by both high-pressure resistivity measurements and ab initio theory.
Gesehen am 22.03.2022